Wild animus - Shapero, Rich.; Coyote, Peter ([Woodside, Calif.] : Too Far, 2005)
"After graduating from college, Sam Altman finds himself disillusioned with the world of the '60s and rejects normal life to follow an inner calling. Altman's unleashed--and increasingly unhinged--imagination takes him first to Seattle and then farther north, to the remote Alaskan wilderness. Sam has fallen deeply in love with the mysterious and powerful Lindy, a young woman who will do anything to help him realize his quest, no matter how dangerous. Alone with a driving need to uncover his innermost self, Sam gradually transforms himself into a ram, prey to a pack of strangely familiar wolves. The mad pursuit leads from the wilds to civilization and back again. And when Sam and Lindy return to the perilous mountain together, the truth behind his imagined transformation emerges"--Book description.
Unabridged.
Compact discs.
In container (15 cm.).
Read by Peter Coyote.
Keywords: Metaphysics -- Fiction; Spiritual life -- Fiction; Wrangell-Saint Elias National Park and Preserve (Alaska) -- Fiction